(untitled) (Computer systems and information technologies, 2024)
The article examines the aspects of land surface temperature forecasting for effective planning and development of sustainable cities and communities. The relevance of the research lies in the need to develop effective approaches to the analysis and forecasting of climate data, for the timely determination of existing problems and ways to solve them, in accordance with civilizational challenges. The trends of changes in the land surface temperature from the middle of the 20th to the beginning of the 21st century were analyzed, using the example of five megacities located in different regions: Tokyo (Japan), Lagos (Nigeria), Berlin (Germany), Singapore (Singapore) and Belo Horizonte (Brazil). The results of the analysis of changes in average monthly and average annual temperatures are presented. The factors affecting the formation of the temperature regime of each of the cities are determined. The role of urbanization as a key factor in the development of the city is described, the main challenges caused by it are considered. An overview of megacities from the point of view of sustainable development was carried out. Prospects for urban development and measures aimed at reducing the urban heat island effect are considered. The role of modern technologies, in particular machine learning for predicting the land surface temperature, is described. The expediency of land surface temperature forecasting, in order to implement strategies for mitigating negative consequences and achieving the goals of sustainable development, is substantiated. The conducted research makes it possible to be convinced of the need for a responsible approach to the design and development of sustainable cities and communities. The temperature of the earth’s surface is one of the key indicators that allows you to monitor the main trends of urban life and can be an indicator of the effectiveness of strategies used to increase comfort and sustainable development.